NAVIGATING ACADEMIC WRITING CHALLENGES IN ISLAMIC HIGHER EDUCATION (Jurnal Bahasa Lingua Scientia, 2024)
This study delves into the challenges faced by English Language Education program students in Islamic higher education institutions, focusing on IAIDA and UNUJA. Employing a qualitative case study methodology, the research investigates the factors influencing academic writing skills among final-semester students. Findings reveal intricate challenges, including time management issues due to boarding school commitments, limited technology access, and difficulties in understanding research methodology. Challenges in finding and managing references, alongside the impact of supervisors and external factors, such as financial pressures, are identified. Distinct institutional variations between IAIDA and UNUJA underscore the need for targeted interventions to enhance academic writing skills. The results call for strategic initiatives and curriculum enhancements to address the specific needs of students in Islamic higher education, ultimately facilitating their success in academic writing
Keywords: Academic writing skills, Academic writing challenges, Islamic higher education, Santri, pesantren